Globalization and Modern Identity Practices - Locals and Cosmopolitans in Seventeenth Century Amsterdam - Ufer, Ulrich (HERMES - Journal of Language and Communication in Business, 2009)
This paper offers a historical analysis of cultural identiﬁcation among locals and cosmopolitans in Amsterdam, the centre of the seventeenth century world system. Here, the convergence of global processes and local changes, such as increasing monetization, commodiﬁcation and anonymization of everyday lives generated conditions that contributed to the formation of modern individual and group identities. Early modern globalization gave rise to a “global animus” in Amsterdam and it prompted the city’s political elites to promote a cosmopolitan civic identity, expressed in allegoric art and architecture. On a theoretical level this paper criticizes objectifying or essentializing approaches to cultural globalization and to cultural identity and highlights instead the contradictions and ambiguities involved in the processes of attributing cultural meaning. A discussion of the poetry of Jacob Cats (1577–1660) reveals how local actors attributed contesting cultural meanings to the objects of global trade and how they acculturated them in different ways into their practices of local or cosmopolitan identiﬁcation.